Thermoelectric Materials: Physical Metallurgy Inspired Nano‐Features for Enhancement of Thermoelectric Conversion Efficiency (Adv. Theory Simul. 9/2018). Issue 9 (6th September 2018) - Amouyal, Yaron; Gelbstein, Yaniv; Fuks, David
Abstract : In article number1800072, Yaron Amouyal and co‐workers review approaches to enhance thermoelectric power generation efficiency adapted from physical metallurgy. Second‐phase precipitates dispersed in a thermoelectric matrix affect both thermal and electronic transport. Ab‐initio calculations provide information on structural, vibrational, and electronic behavior of individual phases. In turn, computational thermodynamics yield matrix/precipitate phase equilibria with major implications for materials design.